Harnessing the spatial and transcriptional regulation of monoterpenoid indole alkaloid metabolism in Alstonia scholaris leads to the identification of broad geissoschizine cyclase activities - Méteignier, Louis-Valentin (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2024 The Author(s). Published by Elsevier Masson SAS.. All rights reserved.